Teze prof. dr. Franca Pedička o telesni vzgoji in njihov pomen za današnji čas na področju športne vzgoje - Plavčak, Marjan (Šport (Ljubljana), 2013)
Dr Franc Pediček was a renowned philosopher, psychologist and pedagogue who broadened his work and mission also in the area of physical education, sport and recreation. At the time, his ideas and thoughts were among the most advanced and clearly had a strong influence on the further development of these areas. We believe that some of his thoughts on physical education, sport and recreation can underpin the creation of new ideas and solutions for today. When analysing his theses we established that some are more and some less topical today.
Keywords: anthropology; antropologija; pedagogika; pedagogy; Pediček, Franc, 1922-2008; physical culture; physical education in school; recreation; rekreacija; scientific method; scientific research; sport; sport education in school; šolska športna vzgoja; šolska telesna vzgoja; šport; telesna kultura; znanstveno raziskovanje